2018
DOI: 10.1159/000490740
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes in Conservative versus Surgical Treatments for Ludwig’s Angina

Abstract: Objective: To compare the treatment outcomes in patients with early stage Ludwig’s angina who received intravenous antibiotics alone with those who received surgical decompression and intravenous antibiotics. Subjects and Methods: Individuals with early stage Ludwig’s angina were studied using a retrospective cohort study design from August 1997 to September 2017. Data were collected from case notes and logbooks. Appropriate statistical tests were chosen to analyze both the independent and outcome variables. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 14 publications
0
11
0
5
Order By: Relevance
“…The critically ill patients with LA in our study had a wide age range from 8 to 78 years, which is a wider age range than in previous studies of patients with LA. 11 , 13 This is because children and older adults have low resistance to disease, and are therefore more likely to progress into critically ill patients requiring intensive care.…”
Section: Discussionmentioning
confidence: 99%
“…The critically ill patients with LA in our study had a wide age range from 8 to 78 years, which is a wider age range than in previous studies of patients with LA. 11 , 13 This is because children and older adults have low resistance to disease, and are therefore more likely to progress into critically ill patients requiring intensive care.…”
Section: Discussionmentioning
confidence: 99%
“…These patients may decompensate rapidly, developing complications including aspiration, pneumonia, empyema, mediastinitis, pericarditis, carotid artery or internal jugular vein thrombosis or erosion, and sepsis, (Filippone, 2004). A recent paper comparing outcomes of conservative treatment versus surgical treatment for Ludwig's angina concluded that there was a higher incidence of airway compromise in the conservative treatment approach (Edetanlen and Saheeb, 2018).…”
Section: Conservative Approach To Treatmentmentioning
confidence: 99%
“…He was therefore managed conservatively with extremely close monitoring in the 'resuscitation' area of the department. He was placed on 15l high flow oxygen therapy via a facemask, placed into an upright-seated position on the trolley with continuous cardiac and oxygen saturation monitoring, and IV Metronidazole (500mg) was commenced (Edetanlen and Saheeb, 2018). At this point consideration was given to Mr Jones' observations.…”
Section: Airway Managementmentioning
confidence: 99%
“…2,3 Early surgical drainage supported by medical management being the mainstay of treating Ludwig's angina, decreases the stress on airway and provides better antibiotic penetration. 4 Antibiotic sensitivity testing and culture can aid in administration of culture specific antibiotics. Ludwig's angina requires a complex multidisciplinary approach and this may be further complicated if the patient is positive for COVID-19 because of the need © 2021 Special Care Dentistry Association and Wiley Periodicals LLC for isolation and extensive care to avoid sepsis and airway collapse.…”
Section: Introductionmentioning
confidence: 99%